University proceedings. Volga region. Technical sciences - M.Yu. Babich; V.E. Kuznetsov; M.A. Chigirev; A.M. Babich (Известия высших учебных заведений. Поволжский регион:Технические науки)
Background. The following tasks are set in the work: analysis of the possibility of using emotional agents in SOS models of two groups; development of proposals for the use of emotional agents. The first group of models are deterministic and stochastic models (complete formalization of processes), the second are models with less formalization (Foresight method, situational analysis, etc.). Simulation of emotional states is relevant for systems with incomplete and inaccurate information, when the chosen decisions are often the result of emotions and can be irrational. Materials and methods. Methods that fully formalize emotional processes using modern mathematical apparatus and the possibility of simulating emotions with only partial formalization are considered. Results. It is proposed to use the imitation of the emergence of human emotional states by including certain types of agents in the model. Conclusions. The proposed use of agent types allows us to take into account emotions resulting from events that occurred long before the considered modeling interval in systems located outside the contour of the modeled system